2018
DOI: 10.3389/fonc.2018.00446
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 and miR-183 Promote Cell Proliferation and Invasion by Targeting FOXO1 in Mesothelioma

Abstract: Dysregulation of miR-182 and miR-183 has been implicated in the progression of several human cancers. Our previous study showed that miR-182 and miR-183 are upregulated in malignant mesothelioma. However, their biological functions remain unclear. We performed in-situ hybridization to analyze the expression of miR-182 and miR-183 in human tissues. Functional analysis was performed by treatment of two mesothelioma cell lines (ACC-MESO1 and CRL-5915) with miR-182 and miR-183 inhibitors. RT-PCR and western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 38 publications
(39 reference statements)
2
35
0
1
Order By: Relevance
“…Johnson et al (22) found that a miR-137 mimic inhibited the proliferation, invasion, and migration of mesothelioma cells, and Williams et al (23) found that miR-13 reduced proliferation, and increased apoptosis and necrosis of mesothelioma cells by downregulating MCL1. Further, we demonstrated previously that miR-1 and miR-214 inhibited mesothelioma cell progression by suppressing PIM1 (11,24), and miR-182 and miR-183 promoted mesothelioma cell progression by suppressing FOXO1 (25).…”
Section: Discussionsupporting
confidence: 56%
“…Johnson et al (22) found that a miR-137 mimic inhibited the proliferation, invasion, and migration of mesothelioma cells, and Williams et al (23) found that miR-13 reduced proliferation, and increased apoptosis and necrosis of mesothelioma cells by downregulating MCL1. Further, we demonstrated previously that miR-1 and miR-214 inhibited mesothelioma cell progression by suppressing PIM1 (11,24), and miR-182 and miR-183 promoted mesothelioma cell progression by suppressing FOXO1 (25).…”
Section: Discussionsupporting
confidence: 56%
“…He et al (38) demonstrated that in human osteosarcoma, mir-374a enhanced cell growth by inhibiting downstream FOXO1 signaling, which is consistent with the results of the current study in human ovarian cancer cells. Furthermore, p27 is a CDK inhibitor that has a negative regulatory effect on proliferation and is a downstream target of FOXO1; consequently, FOXO1 inhibits cell proliferation by upregulating p27 (39)(40)(41)(42). The Bim protein belongs to the Bcl-2 protein family and exerts a pro-apoptotic effect on cells (43,44); previous studies have confirmed that FOXO1 regulates cell apoptosis through its downstream targets, including Bim (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Based on database predictions and previous reports, we hypothesized that mTOR and FOXO1 are two important downstream targets of miR-182. 15,47 Existing reports have shown that mTOR can protect cortical neurons by inhibiting apoptosis after OGD. 48 Of note, as an important transcription factor, FOXO1 deficiency causes a wide range of scar formation and infarct area accompanied by downregulation of the ratio of Bcl-2/ Bax following acute ischemia/reperfusion injury.…”
mentioning
confidence: 99%